Analisa Hasil Pengujian Alat Tenaga Listrik Berbasis Wind Turbine di Curug Cigentis Desa Mekarbuana - Sahrul Asrofani; Kardiman Kardiman; Ratna Dewi Anjani (Peneliti.net, 2022)
One of the uses of renewable energy that currently has great potential to be developed is wind energy. This energy is clean energy and in its production process does not pollute the environment. The development of wind energy in Indonesia for now is still relatively low. One of the reasons is that the average wind speed in Indonesia is classified as low wind speed, which ranges from 3 m/s to 5 m/s, making it difficult to generate electricity on a large scale. However, the wind potential in Indonesia is available almost all year round, making it possible to develop small-scale power generation systems